Kitāb al-muʿtamad fī uṣūl al-dīn - al-Malāḥimī, Maḥmūd b. Muḥammad (Miras Maktoob, ISBN: 9789004365452., 2019)
Abu ʼl-Ḥusayn al-Baṣrī (d. 436/1044) was the founder of the last theological school of the Muʿtazila and author of, among others, the Kitāb taṣaffuḥ al-adilla and Sharḥ al-uṣūl al-khamsa . None of his theological works survive in full, while his influential Kitāb taṣaffuḥ al-adilla , of which only fragments remain, was actually never finished. Al-Baṣrī's teachings were given a new impulse and audience through the writings of Rukn al-Dīn b. al-Maḥmūd al-Malāḥimī (d. 536/1141) of Khurāsān, where his ideas also gained support among the Shīʿa, including Naṣīr al-Dīn Ṭūsī (d. 672/1274). Al-Malāḥimī's Kitāb al-muʿtamad fī uṣūl al-dīn , in which he relies mostly on al-Baṣrī's Kitāb taṣaffuḥ al-adilla , survives only in part. The present volume contains a new edition of this text. Thanks to the discovery of two manuscripts in Yemen it was possible to amend the first edition in places and to add a lot of new material, the text now being double in size.